131 WNT5A: A POTENTIAL LINK BETWEEN INFLAMMATION AND MORPHOGENESIS IN BRONCHOPULMONARY DYSPLASIA. Issue 1 (1st January 2007) - Villosis, M. F.; Li, C.; Durand, M.; Ramanathan, R.; Kwong, K. Y.C.; Minoo., P.
Abstract : Introduction: Wnt5a is a signaling molecule that is expressed in both the mesenchyme and the epithelium of the embryonic lung and plays a key role in its morphogenesis. Recently, Wnt5a was found in adult mononuclear cells. Whether inflammatory cells from the lungs of preterm neonates at risk for BPD also express Wnt5a is unknown. Objective: To examine Wnt5a expression in lung inflammatory cells from preterm neonates. Methods: Inflammatory cells (macrophages and neutrophils) were isolated from lungs of human preterm neonates. Cells were incubated in the presence or absence of LPS and Wnt5a mRNA was measured by real-time RT-PCR. Results: Wnt5a was constitutively expressed by lung inflammatory cells from preterm infants. LPS stimulated Wnt5a mRNA in some but not all samples. The magnitude of response correlated with gestational age, birth weight, and positive endotracheal tube and blood cultures. Conclusion: Expression of Wnt5a by lung inflammatory cells may impact on inflammatory cells functions and/or a morphogenetic impact on lung structural development. Supported by NHLBI and the Hastings Foundation .